Water 4.0 : the past, present, and future of the world's most vital resource - Sedlak, David (London: Yale University Press, 2015)
The little-known story of the systems that bring us our drinking water, how they were developed, the problems they are facing, and how they will be reinvented in the near future
In English.
H.B
Keywords: Water resources development History; Ressources en eau Exploitation Histoire; Water-supply engineering History